Pengaruh Iklan Shopeefood Terhadap Minat Beli Konsumen Pada Remaja Palembang - Muhammad Nurfatoni; Hasmawati Fifi; Hartika Utami Fitri (ScidacPlus, 2024)
The writing of this research is motivated by technological advances in business development which cause tighter competition in various media. Various companies in developing their business carry out several advantages and advantages of each which aim to attract consumer shopping interest, one of which is the e-commerce company Shopee in promoting its products through advertisements on the Youtube internet-based media. For this reason, researchers are interested in examining the variables that can influence buying interest in consumers. The title of this research is